A expansão da escola pública primária na Região Oeste do Paraná (1970-1980) - Gomes, Maria Valdeny Ferreira (2012)
This study aims at showing how the expansion of pub lic elementary school in Western Paraná occurred in the 1970s, based on the consequences of national educational policies at the State and regional leve ls. It was considered the most important moment of the developmental model in Braz il, mainly due to the international organization performance and to the O rganization of American States (OAS), through MEC/OAS Project, whose activities si gnificantly determined the conditions and results of such expansion in the mun icipalities that made part of this project. We also consider the process of regional d evelopment that had occurred during the Itaipu Binational plant building and its socioeconomic impact in the region. Brazilian education organization was analyzed in a historiographical perspective and its consequences on Public School expansion. In Cas cavel city, we visited the files of the Education Department from AMOP - Association of Municipalities from the Western Region, the NRE - Regional Education Center and of the school records from two public schools. In Curitiba, the surveys w ere based on data obtained from the Public Archive of Paraná, Paraná Public Library and from the Circle of Bandeirante Study. The main studied references were the documents and primary sources collected at the Education Department Files of AMOP. The expansion of public schools in western regions is a result of re lations among economic power, political power and the relations between State and society. With this study, we intend to contribute to the Regional History of Edu cation and discuss the constitution of the Brazilian public elementary school in Wester n Paraná. Researching the school expansion issue can be a relevant way to understand its construction in the 1970s, because there were several changes in both access t o the schools, by offering jobs and territorial distribution of the school system, and the scope of these services according to the years of school attendance, whose aspects will be associated with other movements of society.